Surrogacy Practices in the Legal Dilemma of the Reproductive Technology Era in Indonesia - Rina, Novia (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2025)
This study aims to examine the legal dilemmas arising from surrogacy practices in the era of reproductive technology in Indonesia, focusing on how these practices unfold amid legal uncertainty and the complexity of social and religious values. This research uses a qualitative method with a field research approach, involving in-depth interviews with medical practitioners, legal experts, religious figures, and couples who have considered or engaged in surrogacy, as well as observations at several fertility clinics in urban areas. The findings reveal that surrogacy practices in Indonesia are carried out discreetly without a clear legal foundation, resulting in various issues such as the uncertain legal status of the child, the potential exploitation of women, and the absence of legal protection for all involved parties. The study also finds sharp differences in perspective among medical, legal, and religious sectors regarding the legitimacy and ethics of these practices. The conclusion of this study emphasizes that Indonesia urgently needs clear and comprehensive legal regulations to govern surrogacy practices in alignment with human rights principles and the moral values of society. The academic contribution of this research lies in its effort to provide an empirical overview of surrogacy practices in the field, and to offer concrete input for the formulation of reproductive legal policies in Indonesia that are more responsive to technological advancements and societal needs.